The Association Between Audit Committee Financial Expert Characteristics and Audit Fees (American Journal of Management, 2022)
Using a sample of 136 Fortune 500 companies for the year 2011 (Post-Dodd Frank Act of 2010 has increased additional scrutiny on the monitoring activities of the audit committee members), we investigate whether certain characteristics of ACFE (number of financial experts, tenure, age, education, and gender) have contributed to increase in audit fees. We assume that audit efficiencies occur in audits of firms with certain ACFE characteristics, possibly contributing to increases in audit coverage and subsequent increase in audit fees. We find that older female ACFE tend to ask for higher audit coverage leading to increased audit fees thereby influencing audit quality.
Keywords: management; audit committee; audit fees; financial expert